Facilities and difficulties in elderly care in the family health strategy - Barros, Terezinha Barbosa de; Maia, Evanira Rodrigues; Pagliuca, Lorita Marlena Freitag (Rev Rene, 2011)
The aim of this work is to present the profile of Family Health Strategy professionals, identifying facilities and difficulties faced in elderly care. It is a descriptive, quantitative research, carried out in Caririaçu/CE/BR, between May and June 2009, using a questionnaire. Out of the 21 professionals who were interviewed most were female nurses aged between 20 and 30 years, 13 of which were specialists. Primary care actions were based on the indicators of the Pact for Life, aiming to reduce hospitalizations and complications caused by falls, diabetes and arterial hypertension, besides promoting immunization, home visits and health education. Most of the professionals report that there are only difficulties in elderly care, they include the elderly low assiduity and need for professional training to interfere in the aging process. We need to develop professional competence focused on the elderly to act in humanization and reception, healthy habits, global assessment, family and social support, perception of fragility and intra-family abuse, drug use, osteoporosis, urinary incontinence, depression, dementia, and AIDS.